287 OCULAR COMPLICATIONS OF PEGYLATED INTERFERON THERAPY IN HEPATITIS C PATIENTS. (1st January 2005) - Friedman, E. S.; Garner, M. J.; Williamson, J.; Dawson, B.; Bird, C. B.; Driscoll, C. J.; Tombazzi, C.; Waters, B.
Abstract : Background: Interferon has been associated with infrequent but potentially severe ocular complications including retinopathy and global rupture. Few data are available for ocular side effects of longer acting pegylated interferons. Aim: To study ocular complications of hepatitis C patients treated with pegylated interferon. Patients: 117 (110 male, 7 female); 60 Caucasian, 57 African-American; 8 with diabetes (DM), 28 with hypertension (HTN), 13 with both DM and HTN, 3 with chronic renal insufficiency, 2 HIV+, 4 liver transplantation. Methods: Retrospective chart review of patients treated between 1/2000-9/2004. Total 63 patients treated with pegylated interferon-α 2a and 54 patients treated with pegylated interferon-α 2b. Patients without renal failure were also treated with ribavirin 1000-120 mg/daily. Patients with DM and HTN were referred for fundoscopic examination. Patients who were symptomatic received fundoscopic examinations during therapy. The frequency, severity and natural history of ocular complications were studied. Results: 46/117 (39.3%) patients had pretreatment screening. 49 patients had HTN or DM. 28/49 (57.1%) patients with HTN or DM had pretreatment screening. 2/46 with pretreatment screening had mild retinopathy (one DM, one neurofibromatosis). 11 patients had ocular complications (9 during therapy, 2 immediately after therapy). 9/11 patients with complications had HTN or DM. 9/49 (18.4%) HTN or DM patients had complications. 2/68 (2.9%) of patients without HTN or DM had complications. Complications: 9/11 with retinopathy, 5/11 with cotton wool spots, 1 with migraine associated visual changes. 6 required discontinuation of therapy due to ocular complications. Only 3 with mild retinal changes were continued on therapy. Both patients with abnormal findings on pretreatment screening had progression of retinopathy on therapy. All patients followed after treatment had resolution of retinopathy. 7/63 (11.1%) patients treated with pegylated interferon-α 2a and 2/54 (3.7%) treated with pegylated interferon-α 2b had ocular complications. 33/63 (52.4%) patients treated with pegylated interferon-α 2a compared to 16/54 (29.6%) treated with interferon-α 2b had HTN or DM. Conclusions: In this series, a large percentage of hepatitis C patients had HTN or DM. Ocular complications were frequent and severe with pegylated interferon treatment. High rates of complications were noted in patients with DM and HTN. Complications generally required discontinuation of interferon and patients ultimately had fundoscopic resolution. Based on these findings, routine screening, particularly of hypertensive and diabetic patients, should be performed prior to pegylated interferon therapy for hepatitis C.